2007
DOI: 10.1097/01.ccm.0000253403.65602.ea
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in lung nitric oxide production after peritonitis in mice with sickle cell disease*

Abstract: Acute peritonitis in SAD mice is associated with a defect in lung nitric oxide production and bioavailability that may participate in the acute systemic and lung vaso-occlusive complications of sickle cell disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…There is no definite explanation for the decreased NO production; we previously suggested that it could result from an increased arginase activity, which uses the same precursor, L-arginine (9,16). Deja and colleagues (27) showed that in critically ill patients with sinusitis and sepsis, maxillary NO production is almost completely suppressed by downregulation of iNOS mRNA.…”
Section: Discussionmentioning
confidence: 95%
“…There is no definite explanation for the decreased NO production; we previously suggested that it could result from an increased arginase activity, which uses the same precursor, L-arginine (9,16). Deja and colleagues (27) showed that in critically ill patients with sinusitis and sepsis, maxillary NO production is almost completely suppressed by downregulation of iNOS mRNA.…”
Section: Discussionmentioning
confidence: 95%
“…One hypothesis for this deleterious effect is that hypoxia‐induced RBC haemolysis in mice that received normal RBCs decreased NO bioavailability. As NO modulates the expression of endothelin receptors, a decrease of NO during a SCD crisis could have upregulated EDN1 expression (Reiter & Gladwin, ; Bartolucci et al , ; Gladwin & Kato, ; Wood et al , ). The benefit of IHP‐RBCs over normal RBCs in BERK mice was also observed on inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, exhaled NO can also be used to indirectly assess airway hyperresponsiveness [51,56,66], or to evaluate other types of lung disorders, e.g. acute lung injury (ALI) [40,52,68], pulmonary vascular diseases [60,61,64], and distal lung inflammation [35,36,38,57,63,65,74]. Repeated exhaled NO measurement in chronic disease models is now possible showing us a concept about using exhaled NO as a predictor for late complication in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Exhaled NO can also be measured non-invasively in awake animal by using a closed chamber, although the mixed exhaled NO is not specific for NO production in lower airway [62]. This method has been successfully applied in both rats [36,43,63,64] and mice [33,51,56,57,62,65]. The closed chamber is connected to the ventilator on one side and the analyzer of NO on the other.…”
Section: Two Approaches To Choose: Invasive or Non-invasivementioning
confidence: 99%